Comparative Study of Glyceryl Trinitrate (GTN) Ointment Versus Lateral Internal Sphincterotomy in Management of Chronic Anal Fissure - Makil Shah, Zia Ul Islam, Javed Iqbal, Muhammad Jafar, Mansour Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the effectiveness of 0.2% glyceryl trinitrate ointment versus lateral sphincterotomy in management of patients with chronic anal fissure. Materials and Methods: This Comparative study was done in Irfan general hospital THQ Charsadda, and the duration of this study were from April 2022 to September 2022. In this study 80 patients with anal fissure were enrolled. All the patients were divided into two group by lottery method. Group A patients were treated by lateral sphincterotomy while group B was treated by ointment of 0.2% glyceryl trinitrate. A predesign questionnaire were used to collect data. Results: Total 80 patients were enrolled equally divided in to two groups. Group A had 29 (72.5%) male and 11 (27.5%) female while group B had 23 (57.5%) male and 17 (42.5%) female with mean age of 40.47±10.94 years. Group A had 18 (45%) mild pain and 22 (55%) had severe pain while group B had 19 (47.5%) mild pain and 21 (52.5%) severe pain. 23 (57.5%) and 25 (62.5%) patients had bleeding before treatment. The final comparison after 6 weeks of treatment shows the 65% of patients healed with the lateral sphincterotomy and 52.5% of patients healed with ointment of glyceryl trinitrate. The healed proportion was measured high for the lateral sphincterotomy treatment as compared to the ointment of GTN. Practical implication: In our study we find that lateral sphincterotomy is more effective so this study will help the clinical practioner to select the better treatment option inorder to cure the anal fissure soon. Conclusion: It is concluded that for the treatment of anal fissure, the lateral sphincterotomy is considered an effective treatment as compared to ointment of GTN. Keywords: Chronic anal fissure; Glyceryl trinitrate ointment; Lateral internal sphincterotomy